Naturalistic nursing - Hussey, Trevor (Nursing philosophy, 2011)
Where nurse education aims to provide an overarching intellectual framework, this paper argues that it should be the framework of naturalism. After an exposition of the chief features of naturalism and its relationship to science and morality, the paper describes naturalistic nursing, contrasting it with some other perspectives. There follows a defence of naturalism and naturalistic nursing against several objections, including those concerning spirituality, religion, meaning, morality, and alternative sources of knowledge. The paper ends with some of the advantages of the naturalistic approach.